Entrepreneurship Program Implementation Practices In Public Universities Of Malaysia And Nigeria A Comparative Study - bakar, Sani Abu (2024)
This research investigated the implementation practice of entrepreneurship program in public universities of Malaysia and Nigeria in comparative approach. Specifically, it focused on three components, namely entrepreneurial curriculum content (EEC), entrepreneurial teaching strategies (ETS) and the entrepreneurial university environment (EUE); purposefully to assess their effects on students’ entrepreneurial intention and the challenges surrounding teaching the program with a view of addressing them. The study employed sequential explanatory strategy under mixed method in which qualitative findings strengthened quantitative results. After collecting data from the total sample of 581 students and 10 lecturers of entrepreneurship using questionnaire and interview as instruments, Statistical Package for Social Science (SPSS) version 25 was employed for the computation. Hence, the quantitative data was analysed using Independent t-test and Regression; while the qualitative data was processed according to Braun and Clarke’s thematic analysis framework. The quantitative results revealed that significant differences exist between the Nigerian and Malaysian universities students’ perceived views on the effectiveness of entrepreneurship curriculum content and university environment, but not on the teaching strategies. Again, it was discovered that only ECC and ETS made the strongest contribution in predicting students’ entrepreneurial intention in Nigeria, while only ECC made the strongest contribution in predicting students’ entrepreneurial intention in Malaysia. Along the same line, qualitative findings supported the quantitative findings on the effectiveness of entrepreneurial curriculum content and xxi explained negative students’ perceived views on the entrepreneurial teaching strategies and the university environment.